Review on corneal perforation among mentally disabled patients in a tertiary center in Melaka, Malaysia - Kalaichelvam, Khavigpriyaa; Yeoh, Shao Yin; Jalaluddin, Juliana (International Journal Of Community Medicine And Public Health, 2023)
Corneal perforation is an ocular emergency arising from various causes of infectious and non-infectious disease. Its management could range from temporising measures to various surgical intervention. This study was done to evaluate the causes and management of corneal perforation among mentally disabled patients in Melaka. Retrospective review was done using the ward admission records from 2019 to 2022. Data gathered from cases with corneal perforation was reviewed. There were total of 15 patients with 8 (53.4%) males and 7 (46.6%) females. Out of these, 10 (66.6%) patients are mentally disabled. Majority of the patients (73%) were more than 50 years old. The visual acuity at presentation was poorer than 3/60 in 12 (80%) patients, out of which 10 (83%) patients are mentally disabled. There was a high proportion of perforation, 12 (80%) caused by infective keratitis which is also the main cause of perforation among disabled patients. Among the mentally disabled patients, 5 patients (50%) underwent evisceration, 4 patients (40%) underwent conjunctival flap and 1 patient (10%) was managed conservatively. Comparing with the patients without disability, 2 (40%) patients underwent tectonic keratoplasty, 2 (40%) patients underwent evisceration and 1 (20%) patient underwent conjunctival flap. People with disabilities experience worse health and poorer access to health care compared to people without disability. The presenting visual acuity in the disabled group is poorer. The main cause of corneal perforation among mentally disabled was infection and the options of treatments mainly were conjunctival flaps and evisceration.